2013
DOI: 10.1080/15265161.2013.812487
|View full text |Cite
|
Sign up to set email alerts
|

A Capabilities Approach to Person-Centered Care: Response to Open Peer Commentaries on “Treating Patients as Persons: A Capabilities Approach to Support Delivery of Person-Centered Care”

Abstract: This is an electronic version of an article published in American JournalOur suggestion that the aspects of healthcare quality associated with 'person-centered care' can be understood as a matter of health services and staff recognising and cultivating a subset of capabilities that we called 'person-al'(Entwistle and Watt 2013) attracted a diverse set of open peer commentaries. Taken together, we think these commentaries highlight the strong potential of the guiding idea to illuminate and help address a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Rather they were limited in their cognitive capacities, restricting and preventing optimal communication and understanding, which was clinically assessed by the ward staff. Therefore, the term to describe the care they received is not a person-centered approach, but rather an alternative term of “person-supportive care” as suggested by Entwistle et al [35]. According to Munthe et al [36], person-centered care is intended to empower and liberate patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather they were limited in their cognitive capacities, restricting and preventing optimal communication and understanding, which was clinically assessed by the ward staff. Therefore, the term to describe the care they received is not a person-centered approach, but rather an alternative term of “person-supportive care” as suggested by Entwistle et al [35]. According to Munthe et al [36], person-centered care is intended to empower and liberate patients.…”
Section: Discussionmentioning
confidence: 99%
“…A CGA should be used to assess, treat, and plan future care with frail older people [8,37,38]. Entwistle et al [35] found that staff must understand patient goals and capabilities, despite the fact that medical and health care policies may occasionally promote initiatives that overlook that patients are people. An earlier study warned health professionals [38] that if they do not understand patient preferences, overlook or misinterpret the person, the consequences could be as harmful as misdiagnosing a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Or to look forward and explore the relationship with some future outcome or behavior, probably also via regression analysis. But we argue that neither of these explorations is appropriate when it involves reducing the preferences of a person, or group of persons, to a set of predictive or predictor variables, since this undermines the fundamental personhood of the preference-bearer [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many definitions of "patient-centered care", it has been broadly conceived as "providing care that is respectful of and responsive to individual patient preferences, needs, and values, ensuring that patient values guide all clinical decisions" [17]. This concept is framed within the "person-centered care" concept, as it considers that planning care strategies not only affects patients' health issues, but also their abilities to cope with them [18].…”
Section: Introductionmentioning
confidence: 99%